Viburcol, Engystol, Lymphomyosot - Bioregulatory Approach in Pediatric Practice - S.V. Popovych (Zaslavsky O.Yu., 2016)
One of the most urgent problems in modern pediatrics and neonatology is the need for drugs, which, along with proven efficacy, also will be maximum safe for a growing child's body. The article presents an overview of publications on clinical studies of combined bioregulatory drugs (CBD) Viburcol, Engystol, Lymphomyosot, Lymphomyosot H by German company Biologische Heilmittel Heel GmbH (hereafter - Heel company), which are widely used in childhood diseases [1-3, 4-9, 11-26]. Scientific and clinical studies show the high efficacy of these drugs, which in some cases is comparable with that of other drugs [4-8]. At the same time, above mentioned CBD have a favorable safety profile and are well tolerated by children [4-9, 11-26].